Printed from https://www.webqc.org

Chemical Equations Balanced on 01/23/25

 Equations balanced on the previous day Equations balanced on the next day
Balance the equation of any chemical reaction
NH4Cl + NaOH = NaCl + H2O + NH3 =>
NH4Cl + NaOH = NaCl + H2O + NH3

V(OH)4Cl + Fe(Cl)2 + HCl = VO(Cl)2 + Fe(Cl)3 + H2O =>
V(OH)4Cl + Fe(Cl)2 + 2 HCl = VO(Cl)2 + Fe(Cl)3 + 3 H2O

Ca(MnO4)2 + H2SO4 + KNO2 = MnSO4 + CaSO4 + KNO3 + H2O =>
Ca(MnO4)2 + 3 H2SO4 + 5 KNO2 = 2 MnSO4 + CaSO4 + 5 KNO3 + 3 H2O

Mg(NO3)2 + KOH = MgH + KO(NO3)2 =>
Mg(NO3)2 + KOH = MgH + KO(NO3)2

NaHCO3 = NaOH + CO2 =>
NaHCO3 = NaOH + CO2

KMnO4 + KOH + K2S2O5 = K2MnO4 + K2SO4 + H2O =>
4 KMnO4 + 6 KOH + K2S2O5 = 4 K2MnO4 + 2 K2SO4 + 3 H2O

Co(X)3 + (NH4)2S = Co2S3 + NH4X =>
2 Co(X)3 + 3(NH4)2S = Co2S3 + 6 NH4X

C12H22O11 + Ca(OH)2 = CH3CH2OH + CO2 + CaO =>
C12H22O11 + Ca(OH)2 = 4 CH3CH2OH + 4 CO2 + CaO

AgNO3(aq) + CuSO4(aq) = Ag2SO4(aq) + Cu(NO3)2(aq) =>
2 AgNO3(aq) + CuSO4(aq) = Ag2SO4(aq) + Cu(NO3)2(aq)

CaCO3 + SO4 = O2 + CaSO4 + CO2 =>
2 CaCO3 + 2 SO4 = O2 + 2 CaSO4 + 2 CO2

CH2CHCHCH2 + KMnO4 + H2O = MnO2 + CH2(OH)CHCHCH2(OH) + KOH =>
3 CH2CHCHCH2 + 2 KMnO4 + 4 H2O = 2 MnO2 + 3 CH2(OH)CHCHCH2(OH) + 2 KOH

NaClO3 + KCl = KClO3 + NaCl =>
NaClO3 + KCl = KClO3 + NaCl

PH3 + NaBH4 = PBH6 + NaH =>
PH3 + NaBH4 = PBH6 + NaH

NaVO3 + H2O2 + H2SO4 = [VO(O2)]2SO4 + Na2SO4 + H2O =>
2 NaVO3 + 2 H2O2 + 2 H2SO4 = [VO(O2)]2SO4 + Na2SO4 + 4 H2O

NaMnO4 + H2SO4 = Na2SO4 + HMnO4 =>
2 NaMnO4 + H2SO4 = Na2SO4 + 2 HMnO4

Ba(OH)2 + NH4Br = BaBr2 + NH4OH =>
Ba(OH)2 + 2 NH4Br = BaBr2 + 2 NH4OH

KMnO4 + KNO2 + KOH = KNO3 + K2MnO4 + H2O =>
2 KMnO4 + KNO2 + 2 KOH = KNO3 + 2 K2MnO4 + H2O

FeBr3 + H2O = Fe(OH)2Br + HBr =>
FeBr3 + 2 H2O = Fe(OH)2Br + 2 HBr

Br + Cl2 = BrCl =>
2 Br + Cl2 = 2 BrCl

Na2B4O7*10H2O + H2O2 + NaOH + H2O = Na2B2(O2)2(OH)4*6H2O =>
Na2B4O7*10H2O + 4 H2O2 + 2 NaOH + H2O = 2 Na2B2(O2)2(OH)4*6H2O

C6H8O7 + C2H6O = C12H20O7 + H2O =>
C6H8O7 + 3 C2H6O = C12H20O7 + 3 H2O

NaN3 = Na + N2 =>
2 NaN3 = 2 Na + 3 N2

SO3(g) + H2O(aq) = H2SO4 =>
SO3(g) + H2O(aq) = H2SO4

CuO + HNO3 = H2O + Cu(NO3)2 =>
CuO + 2 HNO3 = H2O + Cu(NO3)2

K4Fe(CN)6 + PbO2 + HCl = KCl + FeCl3 + PbCl2 + CO2 + HNO2 + H2O =>
2 K4Fe(CN)6 + 49 PbO2 + 112 HCl = 8 KCl + 2 FeCl3 + 49 PbCl2 + 12 CO2 + 12 HNO2 + 50 H2O

KOH + HCl = H2O + KCl =>
KOH + HCl = H2O + KCl

Cu + Zn(OH)2 = Zn + CuOH =>
2 Cu + Zn(OH)2 = Zn + 2 CuOH

H + B = HB =>
H + B = HB

Cr2O7{2+} + H{+} + C2H5OH = H2O + Cr{3+} + C2H4O =>
Cr2O7{2+} + 4 H{+} + 5 C2H5OH = 7 H2O + 2 Cr{3+} + 5 C2H4O

HCl + NaOH = NaCl + H2O =>
HCl + NaOH = NaCl + H2O

NH3 + Cu(OAc)2 = N(OAc)2 + CuH3 =>
NH3 + Cu(OAc)2 = N(OAc)2 + CuH3

HClO3 + LiOH = LiClO3 + H2O = LiClO3 + H2O =>
HClO3 + LiOH = LiClO3 + H2O

Fe + KClO3 + KOH = K2FeO4 + H2O + KCl =>
Fe + KClO3 + 2 KOH = K2FeO4 + H2O + KCl

K2O + B2O3 = K2B4O7 =>
K2O + 2 B2O3 = K2B4O7

NaCHO3 + CH3COOH = NaC2H3O2 + H2O + CO2 =>
NaCHO3 + CH3COOH = NaC2H3O2 + H2O + CO2

NaNO3 + H2SO4 = Na2SO4 + HNO3 =>
2 NaNO3 + H2SO4 = Na2SO4 + 2 HNO3

K2Cr2O7 + K2S + H2O = S + K3Cr(OH)6 + KOH =>
K2Cr2O7 + 3 K2S + 7 H2O = 3 S + 2 K3Cr(OH)6 + 2 KOH

Al(NO3)3*9H2O + CH4N2O = Al2O3 + CO2 + H2O + N2 =>
2 Al(NO3)3*9H2O + 5 CH4N2O = Al2O3 + 5 CO2 + 28 H2O + 8 N2

Al(OH)3 + NaOH = Na(Al(OH)4) =>
Al(OH)3 + NaOH = Na(Al(OH)4)

Al2O3 + H2SO3 = Al2(SO3)3 + H2O =>
Al2O3 + 3 H2SO3 = Al2(SO3)3 + 3 H2O

NH3 + AlCl3 = Al(NH3)3 + Cl2 =>
6 NH3 + 2 AlCl3 = 2 Al(NH3)3 + 3 Cl2

C3H8O3 + Na2SO4 = CO2 + H2O + Na2S =>
4 C3H8O3 + 7 Na2SO4 = 12 CO2 + 16 H2O + 7 Na2S

K2CO3 + CaNO3 = CaCO3 + K2NO3 =>
K2CO3 + CaNO3 = CaCO3 + K2NO3

NaOH + KC8H5O4 = H2O + C8H4O4 + K + Na =>
NaOH + KC8H5O4 = H2O + C8H4O4 + K + Na

Mn + H2SO4 = Mn(SO4)2 + S + H2O =>
3 Mn + 8 H2SO4 = 3 Mn(SO4)2 + 2 S + 8 H2O

K4Fe(CN)6 + PbO2 + HCl = KCl + FeCl3 + PbCl2 + CO2 + HNO3 + H2O =>
2 K4Fe(CN)6 + 61 PbO2 + 136 HCl = 8 KCl + 2 FeCl3 + 61 PbCl2 + 12 CO2 + 12 HNO3 + 62 H2O

CaC2H2 = C2H2Ca =>
CaC2H2 = C2H2Ca

Cu(HSO4)2 + NaOH = CuSO4 + Na2SO4 + H2O =>
Cu(HSO4)2 + 2 NaOH = CuSO4 + Na2SO4 + 2 H2O

Al2C6(s) + H2O(l) = Al(OH)3 + C2H2(g) =>
Al2C6(s) + 6 H2O(l) = 2 Al(OH)3 + 3 C2H2(g)

Fe(OH)3 + H2SO3 = H2(OH)3 + FeSO3 =>
Fe(OH)3 + H2SO3 = H2(OH)3 + FeSO3

1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64
Balance the equation of any chemical reaction
 Equations balanced on the previous day Equations balanced on the next day
Equations balanced on 01/16/25
Equations balanced on 12/24/24
Equations balanced on 01/23/24
Please let us know how we can improve this web app.
Menu Balance Molar mass Gas laws Units Chemistry tools Periodic table Chemical forum Symmetry Constants Contribute Contact us
How to cite?